Considering the effect of pulp chemistry during flotation on froth stability - Sheni, Nanji Ruth (Department of Chemical Engineering, 2017)
On an industrial scale the need for improved flotation performance is of high importance in the current economic climate. Studies have shown that the pulp phase chemistry has a strong effect on the froth phase and therefore it is necessary to investigate how the manipulation of pulp chemistry factors can improve flotation performance. Research into the manipulation of this chemistry is well underway and factors including the pulp potential (Eh), pH, dissolved oxygen (DO) and ionic strength (IS) govern the pulp chemistry. This study aims to investigate how the manipulation of these factors affects the froth stability, bubble size and entrainment of the froth phase through Platinum Group Metal (PGM) flotation. In this study the Eh, pH, DO and IS were successfully manipulated to investigate their effects on froth stability and water recovery in 2-phase, as well as their effect on water and solids recovery, entrainment and the grades and recoveries of valuable minerals (copper, nickel, platinum and palladium) in 3-phase in the absence and presence of depressant at high dosages; 500 g/t Carboxymethyl Cellulose (CMC). Stability column tests were used to determine froth stability as a function of the dynamic stability factor (Barbian et al., 2005) and batch flotation tests were used to obtain the total water and solids recovered, the grades and recoveries of the valuable minerals as well as to determine entrainment. Further tests were performed to investigate the effect of changing the pH on the Eh in a 3-phase system in which all the other pulp factors were kept constant. The effect of changing the pulp factors on the froth bubble size was investigated by capturing side view images of the froth obtained in a batch flotation cell as each pulp factor was changed. This study has shown that careful control of the pulp chemistry, namely increasing IS, increasing pH, decreasing DO and decreasing Eh, resulted in improved froth stability. The Eh was found to be inversely proportional to the pH. This study has further shown that increased water recoveries and reduced bubble size in the froth were observed at 5 IS as compared to 1 IS due to the froth stabilising nature of the pulp at 5 IS. Operating at high Eh (500-730 mV) was observed to be detrimental to valuable mineral grades and recoveries and promotes entrainment. This kind of knowledge contribution may be key in improving flotation performance and increasing the grades and recoveries of valuable minerals obtained in South Africa's PGM mining industry.